IMPACT OF ECONOMIC GROWTH ON FOOD SECURITY IN NIGERIA: A TIME SERIES ANALYSIS (1981-2024) - Shamaki, I.S.; Ojoko, E.A.; Danmusa, A.H. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study investigates the impact of economic growth on food security in Nigeria using time-series data from 1981 to 2024, sourced from the Central Bank of Nigeria (CBN) and the World Bank’s World Development Indicators (WDI). The methodology includes trend analysis, the Autoregressive Distributed Lag (ARDL) bounds test, and the Vector Error Correction Model (VECM). The trend analysis shows that Nigeria's population growth rate decreased from 2.8% in 1982 to 2.1% in 2024, driven by improved education and socioeconomic development. Unit root tests confirm mixed stationarity at I(0) and I(1), while the ARDL bounds test establishes a long-run cointegration relationship (F-statistic of 6.455). Long-run estimates indicate that Real Government Expenditure (∆ TGEX) significantly increases food security, with a one-unit rise yielding a 0.156-unit improvement. In the short run, the model exhibits a good fit (R2 = 0.742), with an adjustment speed of 61% toward long-run equilibrium. While current government spending positively impacts food security, lagged expenditure shows a negative effect, emphasizing the need for sustained long-term investments over short-term interventions. The study concludes that economic growth has a positive and significant long-run effect on food security but a negative short-run effect. To ensure food sufficiency, the study recommends expanding and mechanizing large-scale agricultural production using modern technology.